Impact of Work Accident Rate on Construction Safety Management System: A Case Study in Sidoarjo, Indonesia - Maulidya Octaviani Bustamin; Eko Wijaksono; Wisnu Abiarto N (Universitas Negeri Semarang, 2026)
Zero Accident is a concept that aims to eliminate work accidents by implementing an effective Construction Safety Management System (CSMS) in accordance with applicable regulations. The CSMS is very important for creating safety and security for all parties involved, as well as the work environment. However, during implementation, many contractors do not adhere to the applicable rules and guidelines; therefore, this research was conducted to examine how the current occupational safety management system is implemented in the field. This study focuses on the results of the analysis of the accident work rate in the Sidoarjo Integrated Central Building construction project. Based on the results of the analysis, it was found that the contractor's commitment to implement the work safety plan had a great impact on the implementation of the construction safety management system of this project, even obtained, with 0 Frequency Severity Indicator per 1,000,000 working hours of people, successfully implemented by the contractor. This result allows the work to be implemented simultaneously in accordance with the plan, on time, with quality, and at cost, because there are no work accidents that affect it, and the contractor can avoid negative costs associated with them.